Analisis Kontrastif Verba Oriru dalam Bahasa Jepang dan Verba Turun dalam Bahasa Indonesia (NAWA: Journal of Japanese Studies, 2025)
This study aims to explain the structure and meaning of the verb oriru in Japanese, the structure and meaning of the verb turun in Indonesian, as well as to identify the similarities and differences between them. The data for this research were obtained from various online sources, such as linguistic corpora, Liputan6, Suara Merdeka Online, and others. This research employs a qualitative descriptive method. The observation method with note-taking technique was used for data collection. For data analysis, a contrastive technique was applied and the results were further classified. Based on the analysis, the verb oriru in Japanese is classified as an intransitive verb that can form part of a phrase and can conjugate to form compound verbs. The verb oriru has one core meaning and eight extended meanings. Meanwhile, the Indonesian verb turun is also an intransitive verb that can be used in phrases and conjugated into compound verbs. It has one core meaning and thirteen extended meanings. The similarities between oriru and turun are: (1) Both are intransitive verbs; (2) Both can be part of a phrase; (3) Both can conjugate and form compound verbs; (4) Three meanings of oriru and three meanings of turun share semantic equivalence. As for the differences, there are seventeen semantic distinctions between the two verbs.